The Influence of Directive Leadership Style, Motivation, and Discipline on Performance Personil Kompi 1 Batalyon B Pelopor Brimob Sumbawa - Nurdin, Nurdin; Yamin, Ahmad; Insan, Imammul (Empiricism Journal, 2022)
Performance really needs to be considered, where performance is used as an expression of a person's ability to carry out a job. Good performance can be seen from the directive leadership style. Where leadership style is the way a leader influences the behavior of subordinates, so they are willing to work together and want to work productively to achieve organizational goals. In addition to leadership style, motivation is also needed in improving performance. Then performance can also be influenced by the discipline of human resources in the environment. This research was conducted at Company 1 Battalion B Pioneer, where there are still obstacles in improving the performance of its personnel including those related to directive leadership, where there are still Company 1 Battalion B Pioneer personnel aged over 40 years and in rank (Nintara and Tamtama) as well. many senior personnel. So this study aims to analyze the influence of directive leadership style, motivation, and discipline on the performance of Company Personnel 1 Battalion B Pioneer – Brimob Sumbawa. This research is a quantitative research. The sampling technique used by the researcher is a saturated sample, that is, the entire population is used as a sample. Where the number of personnel of Company 1 Battalion B Pioneer – Brimob Sumbawa is 120 personnel. Data collection techniques carried out by researchers by distributing questionnaires. The data were analyzed using a statistical software (statistical software) in the form of a statistical package for social science (SPSS) application. Based on the results of the study, it can be concluded that: 1) The directive leadership style has no effect on the performance of the personnel of Company 1 Battalion B Pioneers – Brimob Sumbawa; 2) Motivation affects the performance of Company 1 Battalion B Pioneer personnel – Brimob Sumbawa; 3) Discipline affects the performance of Company 1 Battalion B Pioneer personnel – Brimob Sumbawa